Basic Chemistry Practicum Handbook with Occupational Health and Safety (K3) to Prevent Work Accidents in Laboratory: Validity and Feasibility - Sudiana, I Ketut; Suja, I Wayan (Universitas Pendidikan Ganesha, 2021)
First year students of the Chemistry Education Study Program have some problems in practicum because the students' basic laboratory skills are low. The current practicum guide is not sufficient to provide information on basic skills for working in the laboratory. This condition causes students to have problems practicum and there is a potential risk of accidents. This study aims to produce a handbook for Basic Chemistry I with Occupational Health and Safety (K3) which is feasible to be implemented in Basic Chemistry Practicum I. This research was a Research and Development (R&D) with a 4-D development model, consist of 4 main stages, Define, Design, Develop and Disseminate. The research was limited to the development stage, which ended in the legibility test. Based on expert assessment the results showed that the handbook for Basic Chemistry Practicum I with K3 was very valid in terms of content (3.75), language (3.70), and media (3.6) from a maximum score of 4. The results of the readability test from 9 students showed that all students gave clear assessments. They understood the contents and guidelines for practicum on Basic Chemistry 1 with K3 very well. The conclusion of this study is Basic Chemistry Practicum I Handbook with K3 content is valid to be implemented from the aspects of content, presentation, language, media, and readability.